2019
DOI: 10.1111/1744-7917.12665
|View full text |Cite
|
Sign up to set email alerts
|

Dim artificial light at night reduces the cellular immune response of the black field cricket, Teleogryllus commodus

Abstract: A functioning immune system is crucial for protection against disease and illness, yet increasing evidence suggests that species living in urban areas could be suffering from immune suppression, due to the presence of artificial light at night (ALAN). This study examined the effects of ecologically relevant levels of ALAN on three key measures of immune function (haemocyte concentration, lytic activity, and phenoloxidase activity) using a model invertebrate species, the Australian black field cricket, Teleogry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…ALAN-exposed nestlings tended to have a smaller increase of haptoglobin levels compared with dark-night nestlings. Previous laboratory experiments on light exposure and immune responses suggested that animals kept for several weeks under mostly constant light conditions show weaker immune responses, which corroborates our findings in a wild population (crickets: Durrant et al, 2020 ; chickens: Kirby and Froman, 1991 ; quails: Moore and Siopes, 2000 ). While baseline haptoglobin levels were not affected by the ALAN exposure treatment, there was a trend that our ALAN treatment groups differed post-immune challenge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ALAN-exposed nestlings tended to have a smaller increase of haptoglobin levels compared with dark-night nestlings. Previous laboratory experiments on light exposure and immune responses suggested that animals kept for several weeks under mostly constant light conditions show weaker immune responses, which corroborates our findings in a wild population (crickets: Durrant et al, 2020 ; chickens: Kirby and Froman, 1991 ; quails: Moore and Siopes, 2000 ). While baseline haptoglobin levels were not affected by the ALAN exposure treatment, there was a trend that our ALAN treatment groups differed post-immune challenge.…”
Section: Discussionsupporting
confidence: 91%
“…Pinealectomy, and thereby reduced melatonin levels, results in delayed development of immune tissues and function in birds ( Jankovíc et al, 1994 ). Exposure to ALAN in laboratory settings suppresses immune responses in rodents ( Bedrosian et al, 2011 ; Oishi et al, 2006 ), birds ( Moore and Siopes, 2000 ) and invertebrates ( Durrant et al, 2020 ). Moreover, administration of exogenous melatonin reverses or mitigates the detrimental effects of ALAN on the immune system ( Jones et al, 2015 ; Moore and Siopes, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is suppressed at very low light intensities, as little as 6 lux in sensitive humans [12], although a large range in human sensitivity to this effect has been observed [93]. The long-term health impacts of ALAN exposure are presently unknown, but it is suspected that chronic exposure to even dim ALAN has cumulative effects comparable to those from higher illuminances [94]. Some of the direct and downstream health impacts of exposure to ALAN may include stress, obesity, incidence of certain cancers, and illnesses related to sleep deprivation.…”
Section: Policy and Societymentioning
confidence: 99%
“…Approximately one-tenth of the world's population (600 million people) live in coastal areas that are less than 10 m above sea level, resulting in considerable anthropogenic light pollution [ 7 ], which is expected to increase in parallel with global human population increases along the world's coastline [ 8 ]. Light pollution is a recognized threat for wildlife and biodiversity worldwide [ 9 , 10 ], directly affecting biological and ecological processes across taxa, including changes in key life-history traits, such as immune function [ 11 , 12 ], survival [ 13 ], ageing [ 14 ], and fecundity [ 15 ], however, the impacts of ALAN have rarely been assessed for marine species in the wild.…”
Section: Introductionmentioning
confidence: 99%